2012
DOI: 10.1037/a0025750
|View full text |Cite
|
Sign up to set email alerts
|

The own-age bias in face recognition: A meta-analytic and theoretical review.

Abstract: A large number of studies have examined the finding that recognition memory for faces of one's own age group is often superior to memory for faces of another age group. We examined this own-age bias (OAB) in the meta-analyses reported. These data showed that hits were reliably greater for same-age relative to other-age faces (g = 0.23) and that false alarms were reliably less likely for same-age compared with other-age faces (g = -0.23). Further meta-analyses of measures of signal detection demonstrated that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
324
9
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(365 citation statements)
references
References 135 publications
(281 reference statements)
30
324
9
2
Order By: Relevance
“…Thus, although face age did not influence gaze-cuing in the supraliminal task, both young and older adults followed the gaze of subliminal faces more readily when they were older rather than young. Thus, our findings were not consistent with Slessor et al's (2010) finding that only young participants demonstrate own-age biases in gaze following, and were only partly in line with the own-age bias demonstrated by both young and older adults in face recognition (Rhodes & Anastasi, 2012).The data suggest that older adults may benefit from a reduction in demands for conscious, deliberative processing when achieving joint attention with own-age faces that potentially represent more desirable interaction partners (Ebner et al, 2013;Wright et al, 2008). …”
contrasting
confidence: 56%
See 1 more Smart Citation
“…Thus, although face age did not influence gaze-cuing in the supraliminal task, both young and older adults followed the gaze of subliminal faces more readily when they were older rather than young. Thus, our findings were not consistent with Slessor et al's (2010) finding that only young participants demonstrate own-age biases in gaze following, and were only partly in line with the own-age bias demonstrated by both young and older adults in face recognition (Rhodes & Anastasi, 2012).The data suggest that older adults may benefit from a reduction in demands for conscious, deliberative processing when achieving joint attention with own-age faces that potentially represent more desirable interaction partners (Ebner et al, 2013;Wright et al, 2008). …”
contrasting
confidence: 56%
“…Although a meta-analytic review demonstrated that both young and older age groups experience own-age biases (Rhodes & Anastasi, 2012), this was specifically with respect to recognition memory for faces, which may differ from social perception and, more specifically, gaze cuing.…”
Section: Discussionmentioning
confidence: 99%
“…A similar effect has also been shown with age; faces similar in age to ones own receive more attention than those of a dissimilar age (Ebner at al. 2013;Rhodes & Anastasi, 2012). How these factors may influence children's overall judgments of gaze remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Own-age effects on recognition memory have been explained by higher expertise due to a higher quantity of contact with same-aged individuals (Harrison & Hole, 2009;Rhodes & Anastasi, 2012;Wiese et al, 2012;Wiese, Wolff, et al, 2013;Wolff et al, 2012). As an alternative or additional explanation, the own-age effect may be related to the quality of contact, to motivational processes, and to higher identification with the own-age group (Hugenberg, Young, Bernstein, & Sacco, 2010;.…”
mentioning
confidence: 99%